Effect of Filler and Curing Agent on Mechanical, Damping Properties and Heat Resistance of Ethylene Propylene Diene Rubbers - Youn Park, Hae; Kyeong No, Tae; Guk Kang, Dong; Sik Seo, Jae; Mo Yang, Kyung; Ho Seo, Kwan (Asian Journal of Chemistry, 2013)
Ethylene propylene diene rubber has been used for damping applications owing to its high tan d value. This study measured the mechanical and damping properties of tyre compounds containing ethylene propylene diene rubber. High abrasion furnace black, semi-reinforcing furnace black, acetylene black and black pearl were used as fillers. Sulfur and dicumyl peroxide were used as curing agents. The mechanical and damping properties of compounds with ethylene propylene diene rubber and carbon black were examined and the effects of the curing agent on these compounds were observed. The measurements were carried out using a durometer, universal testing machine and dynamic mechanical analysis. The tensile strength and hardness increased with decreasing ethylene concentration in ethylene propylene diene rubber. In addition, the effects of carbon black and the curing agent for ethylene propylene diene rubber were examined. The tensile strength increased and the compression set improved when black pearl was added as a filler to ethylene propylene diene rubber. The tan d of ethylene propylene diene rubber was enhanced by curing with dicumyl peroxide.